River God - Smith W. Wilbur (Macmillan Guided Readers. Moderns)
At the festival of Osiris, loyal subjects of the Pharaoh gather to pay homage to their leader. Only Taita - a wise and formidably gifted eunch slave - sees him as a symbol of the kingdom's fading glory. Danger surrounds all those who oppose the ruling elite.